FORMATION OF THE FINANCIAL TECHNOLOGY MARKET IN THE WORLD ECONOMY AT THE PRESENT STAGE - DUNSKA, Alla; LAGODIIENKO, Vladislav; TKACHENKO, Andrii (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The current stage of development of the world economy is characterized by the process of increasing the role of the financial sector, as well as the transition to a new phase of development - innovation. Globalization in financial innovations is critical in international innovative development in today’s conditions. The rapid spread of financial innovations under the conditions of financial globalization has become the main driver of the formation of the world economic system, contributing to the deepening of financial globalization. The formation of the financial services market is uneven because various factors influence it, including the level of development of information and communication technologies, the stability of the financial sector, and others. These factors have been studied by researchers, but the development of specific segments of the fintech market has its peculiarities. Fintech is a complex system that unites the sectors of new technologies and financial services, startups, and the relevant infrastructure. The financial services sector is increasingly actively using new technologies and tools to perform its functions and implement fundamentally new solutions in which consumers of services are interested. New technologies inherently changed not only the historically formed landscape of providing financial services, giving it freshness and dynamics, but also changed the attitude to such a concept as "money", realizing the transition from cash to virtual money in a reasonably short period. The industry provides subjects of financial relations with a wide range of innovative technologies, among which robotics, biometrics, remote banking, P2P lending, and many others have become vital. The fintech industry is expected to grow due to increased market penetration rates for existing services and their international expansion. The transition from the traditional financial services system to a digital one provides excellent opportunities for large financial companies and FinTech startups to work with banks or financial organizations. As more critical financial infrastructure projects come into production, more players will be interested in implementing digital financial technologies.